1979
DOI: 10.1103/physrevb.19.5495
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance ofNd3+andGd3+

Abstract: We report on the ESR of the rare-earth ions Nd +, Gd +, Er +, and Yb + on powdered samples of various intermetallic compounds of AB2 cubic structure where 8 is a transition-metal ion belonging to the group VIII of the Periodic Table, and A is a nonmagnetic ion (La, Ce, 'Y). The resonance of the Nd + in these compounds originates within a 16 crystal-field ground level and exhibits resolved hyperfine satellites for the ' Nd and ' Nd isotopes. The Gd + spectra show a single isotropic line. Using our data for Gd +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…This analysis does not consider any direct Yb 3+ spin-phonon contribution. 18 The S and Q-band ⌬H͑T͒ data for 7 Շ T Շ 20 K also show exponential behaviors with c Ϸ 200͑70͒Oe/ K and ␦ Ϸ 75͑20͒ K. ␦ Ϸ 65͑30͒ K. 18 The inset of Fig. 3͑a͒ includes b͑͒ for the S and Q bands and inset of Fig.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…This analysis does not consider any direct Yb 3+ spin-phonon contribution. 18 The S and Q-band ⌬H͑T͒ data for 7 Շ T Շ 20 K also show exponential behaviors with c Ϸ 200͑70͒Oe/ K and ␦ Ϸ 75͑20͒ K. ␦ Ϸ 65͑30͒ K. 18 The inset of Fig. 3͑a͒ includes b͑͒ for the S and Q bands and inset of Fig.…”
Section: Methodsmentioning
confidence: 97%
“…The third is the relaxation, also via an exchange interaction with the ͑ce͒, of a thermally populated Yb 3+ excited crystal-field state at ␦ K above the ground state. 18 The fitting parameters are in the inset of Fig. 2͑a͒.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The electronic contribution to the heat capacity of these compounds yields to the ␥ values shown in Table I. In a free c-e gas model ␥ϭ(2/3) 2 k 2 (E F ).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…5 It has been suggested that a negative effective exchange for RE impurities in some d-band compounds is due to the lack of orthogonality between the 4 f and d-orbitals of the neighbor sites. 5,6 The purpose of this paper is to show that ESR of Gd 3ϩ and Nd 3ϩ in the LuInA 4 (AϭCu,Ni) compounds can provide a means to probe the band structure of these systems. We showed that the ESR data of Gd 3ϩ in LuInCu 4 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%